Multinucleated stromal giant cells in the gastroesophageal junctional and gastric mucosa: a retrospective study - Taha Sachak; Wendy L. Frankel; Christina A. Arnold; Wei Chen (BMC, 2019)
Abstract Background Atypical multinucleated stromal giant cells (MSGCs) are occasionally encountered in the esophagogastric mucosa. This study aims to investigate the origin and clinical association of MSGCs in the upper gastrointestinal tract. Methods Three hundred sixty-one contiguous biopsies and 1 resection specimen from the stomach and gastroesophageal junction (GEJ) were identified from archives for morphologic and immunohistochemical studies. Results MSGCs were identified in 22 cases (6%: 7 gastric, 15 GEJ). Patients' average age was 53 years. There was no sex predilection. 77% cases had only 1 or 2 MSGCs per 10 high power fields. MSGCs were located in the lamina propria of the gastric or GEJ mucosa, with an accentuation in the subepithelial zone. The median number of nuclei in a MSGC was 5 (ranging from 3 to 16). The nuclei were touching/overlapping, often arranged into "wreath", "caterpillar", or "morula" configurations. MSGCs expressed smooth muscle actin, desmin, while negative for cytokeratin AE1/3, CD68, S100, chromogranin, and CD117. The most common clinical history was epigastric pain, gastroesophageal reflux, and Barrett esophagus. The most common associated pathologic diagnoses included reactive (chemical) gastropathy (71% gastric biopsies) and gastroesophageal reflux (73% GEJ specimens). Conclusions MSGCs in the esophagogastric mucosa show smooth muscle/myofibroblast differentiation by immunohistochemistry and likely represent a reactive/reparative stromal reaction associated with gastroesophageal reflux and reactive (chemical) gastropathy.